2023
DOI: 10.1038/s41598-023-29652-3
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing-based analyses of drug-resistant Mycobacterium tuberculosis from Taiwan

Abstract: Drug-resistant tuberculosis (DR-TB) posed challenges to global TB control. Whole-genome sequencing (WGS) is recommended for predicting drug resistance to guide DR-TB treatment and management. Nevertheless, data are lacking in Taiwan. Phenotypic drug susceptibility testing (DST) of 12 anti-TB drugs was performed for 200 Mycobacterium tuberculosis isolates. WGS was performed using the Illumina platform. Drug resistance profiles and lineages were predicted in silico using the Total Genotyping Solution for TB (TGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Clinical trials have been conducted to identify the most appropriate PAS-containing regimens for patients with MDR-TB or XDR-TB ( 15 , 16 ). In the current clinical research, WGS is increasingly employed in lieu of traditional susceptibility methods to diagnose second-line drug resistance in TB ( 17 19 ). However, PAS resistance based solely on WGS is challenging, as some PAS resistance mechanisms remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have been conducted to identify the most appropriate PAS-containing regimens for patients with MDR-TB or XDR-TB ( 15 , 16 ). In the current clinical research, WGS is increasingly employed in lieu of traditional susceptibility methods to diagnose second-line drug resistance in TB ( 17 19 ). However, PAS resistance based solely on WGS is challenging, as some PAS resistance mechanisms remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…An isolate with rpoB_p.His445Leu mutation, which was tested as susceptible at rifampicin critical concentration of 1.00 µg/mL showed resistance at a lower rifampicin concentration of 0.5 µg/mL and prolonged incubation ( 10 ). Isolate with the rpoB_Leu430Pro mutation were reported to exhibit MICs ≤ 1 µg/mL ( 54 ). An isolate with rpoB_p.Ser441Leu mutation was also reported to have a MIC of 0.25 µg/mL ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…katG_p.Ser315Thr was the most frequently identified mutation among the isoniazid-resistant isolates in our study, and high phenotypic concordance was observed in isolates having katG_p.Ser315Thr mutation alone or coexisting with other isoniazid DR variants. The majority of the isolates with only katG_p.Ser315Thr mutation showed MICs ≥ 0.5 µg/mL and a small proportion of isolates exhibited MIC <0.1 µg/mL ( 54 ). Other previously reported low-frequency missense mutations such as katG_p.Ser315Asn and katG_p.Asp419His were also observed at a low frequency in our study with a phenotypic concordance of 66.7% and 100%, respectively ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…From existing reports with corresponding NCBI-BioProjects PRJNA879962, PRJEB41116, PRJEB32684, PRJNA379070, and PRJEB29435, Mtb WGS data (n=2601) from India, China, Pakistan, and Zambia were downloaded from the SRA-NCBI database using fasterq-dump v2.11.3 of the SRA Toolkit (NCBI) (1923). Megahit assembler v1.2.9.…”
Section: Methodsmentioning
confidence: 99%